The effect of uremia patients with fistula protector on autogenous fistula maturation - MA Zhi-ying; YANG Ding-ping (Linchuang shenzangbing zazhi)
Objective To study the effect of fistula protector on the autogenous AVF in uremia patients.Methods Select 64 ESRD inpatients with the(forearm) Arteriovenous fistula plastic operation in 2013.9~2014.9,male 36,female 32,age range from 25 to 75 yeas old,average age was(50.2± 10.5).Primary illness:20 cases of diabetes,18 cases of chronic nephritis,14 cases of high blood pressure,6 cases with obstructive nephropathy,6 cases of polycystic kidney.Distributed into treatment group and control group in random method,each group has 32 cases.It was operated by a same surgeons with identical surgical methods(radial artery-cephalic vein end-to-side anastomosis).After the operation the forearm fistula protector was cared by the treatment group,put the inner forearm fistula protector before the chest when the patient standing.When the patient sleeping hang the baldric on the infusion support Keep the art of limb above the 10 cm of the heart.The control group was treated with routine nursing care.Take away from anastomotic 4 cm for the observation point after 6weeks,use the Doppler ultrasound probe head to detect of venous diameter,Blood flow per minute,then compare them.Assessment of two groups of internal fistula rate of mature depends on the NKFK/DOQI clinical practice guidelines.Compare two groups of patients with complications and quality of life.Results The treatment group vascular diameter,blood flow were better than the control group after procedure in 6 weeks(P<0.05).The internal fistula rate of mature was 96.9%of the trearment group after procedure in 6 weeks.The control group was 78.1%.The treatment group was better than the control group(P<0.05).The rate of the vascular stenosis,thrombosis and swelling of the hands of the treatment group is lower than the control group(P<0.05).The treatment group’s patients quality of life was better than the control group(P<0.05).Conclusions Forearm fistula protector notably decreases incidence of fistula’s complications in AVF patients.It has a positive significance in improving blood flow of AVF and fistula maturation.